A Comprehensive Review on Neturaceuticals in Alzheimer's and Neurodegenerative Disease an Cognitive Enhancement - Mohd. Wasiullah; Piyush Yadav; Anita Yadav; Dileep Kumar Yadav (International Journal of Brain Sciences, 2025)
Neurodegenerative diseases, including Alzheimers disease (AD), Parkinsons disease (PD), and related cognitive disorders, represent a significant and growing public health challenge, particularly in aging populations. Despite advances in pharmacological treatments, therapeutic options for cognitive decline and neurodegeneration remain limited. Recent interest has shifted towards nutraceuticals— bioactive compounds derived from food or natural sources—as promising adjuncts or alternatives in the management of these conditions. This review examines how nutraceuticals can help prevent and treat neurodegenerative illnesses, with a focus on their mechanisms of action, efficacy, and therapeutic potential. Numerous bioactive compounds found in natural foods and medicinal herbs have been shown to enhance cognitive function, including memory, attention, and learning. These substances affect cellular functions like neurogenesis, synaptogenesis, synaptic transmission, neuroinflammation, oxidative stress, and neuronal survival as well as brain metabolism. Furthermore, nutraceuticals can promote neuroplasticity, neuroprotection, and cognitive enhancement by modulating key pathways involved in brain function. The ability of nutraceuticals to influence these diverse biological processes underscores their potential as effective agents for brain health. As such, food-based strategies, including dietary supplements and functional foods enriched with nutraceuticals, represent a promising approach to improving cognitive function and potentially mitigating the impact of neurodegenerative diseases.
Keywords: Alzheimer’s disease (AD); Neuroprotective; Neutraceuticals; Phosphatidylserine; cognitive decline; neurodegenerative diseases